Investigating the effective factors influencing surface runoff generation in urban catchments – A review - Rezaei, Abdul Razaq; Ismail, Zubaidah; Niksokhan, Mohammad Hossein; Ramli, Abu Hanipah; Sidek, Lariyah Mohd; Dayarian, Muhammad Amin (Desalination Publications, 2019)
The natural water cycle in an urban catchment normally results from climate, physical characteristics and natural surface coverage. The hydrological process in urban catchments can drastically change due to urbanization, human activities, modified physiography and climate change. Urbanization typically results in a larger runoff volume, higher peak discharge, faster time of concentration as well as lower infiltration. It also has a significant impact on the precipitation intensity and patterns. Antecedent soil moisture, steep slopes and roughness will lead to uncertain rainfall-runoff behavior as well. Climate change will usually alter temperature, precipitation intensity and duration along with the runoff timing and magnitude. Various number of studies have proved that urbanization and climate change would have stronger effect on urban rainfall-runoff behavior than other factors. We have reviewed and investigated various and the most effective factors influencing urban runoff generation in this paper. Particularly, the anthropogenic, geomorphologic and meteorological impacts on urban surface runoff have been the focus of this review paper. The study gaps and suggestions for further research have also been discussed at the end. Finally, the best measures to be taken into consideration to mitigate urban excess runoff have been suggested in the final section. © 2019 Desalination Publications. All rights reserved.